Modelos vs. prácticas. Acercamiento inicial a la cuestión tecnológica en algunos manuales sobre caficultura, 1774-1895 - Samper Kutschbach, Mario (1994)
The study offers an initial comparison of the explicit and implicit technological models suggested or assumed by the author of a series of general treatises, manuals and studies on coffee, both by Europeans or North Americans and by Caribbeans or Latin Americans. Technical recommendations are also contrasted with the various agricultural and processing systems actually in use, as reflected in the pages of those same texts.